The relation between nurses' quality of work life with intention to leave their job - Obeidollah Faraji; Ghader Salehnejad; Shahin Gahramani; Sina Valiee (Tehran University of Medical Sciences, 2017)
Background & Aim: Nurses' intention to leave their job is problematic for health system and the quality of work life is one of the important factors affecting this intention. The present study was aimed to show the nurses' quality of work life and its components, their intention to leave the job, and the relation between nurses' quality of work life and their intention to leave the job. Methods & Materials: This cross-sectional study was conducted on a sample of 300 nurses in teaching hospitals of Kurdistan University of Medical Sciences which were selected through census method. Walton's quality of work life (1988) questionnaire and intention to leave questionnaire designed by Rusbelt et al (1980) were used to collect the data. SPSS 16 software, analytical and descriptive statistics, and statistical tests such as ANOVA, Tukey's HSD test, Independent T-Test and Pearson's correlation coefficient were used to analyze the data. Results: The results showed that 61% of nurses had low levels of work life quality and 39.7% of the nurses intended to leave their job. Intention to leave job was significantly related to the employment status (P=0.01) and gender (P=0.03). Also, there was a significant and inverse correlation between the quality of work life components and intention to leave the job (P=0.0001). Conclusions: Nursing administrators must adopt effective strategies to create favorable working conditions under which nurses' work life quality in different aspects would be improved. To prevent the nurses' from leaving their job, nursing managers should administer interventions to improve the atmosphere of organization that affect the components of working life quality.